5-Hydroxytryptamine, Glutamate, and ATP: Much More Than Neurotransmitters - Franco, Rafael; Rivas-Santisteban, Rafael; Lillo, Jaume; Camps, Jordi; Navarro, Gemma; Reyes-Resina, Irene (Frontiers in Cell and Developmental Biology, 2021)
5-hydroxytryptamine is derived from an amino acid, L-tryptophan, which must be obtained through the diet. Although the compound has been studied extensively for its neuronal handling and synaptic actions, serotonin receptors can be found extra-synaptically and not only in neurons but in many types of mammalian cells, inside and outside the central nervous system (CNS). In sharp contrast, glutamate (Glu) and ATP are better known as metabolism-related molecules, but they also are neurotransmitters, and their receptors are expressed on almost any type of cell inside and outside the nervous system. Whereas 5-hydroxytryptamine and Glu are key regulators of the immune system, ATP actions are more general. Also, whereas 5-hydroxytryptamine acts through (at least) 11 types of G protein-coupled receptors (GPCRs), ATP or Glu receptors may be metabotropic, i.e. GPCRs, or ionotropic, i.e. ligand gated ion channels. These are the three examples of neurotransmitters whose actions as holistic regulatory molecules are briefly put into perspective here.